FMRP Associates with Cytoplasmic Granules at the Onset of Meiosis in the Human Oocyte. - Roseanne Rosario; Panagiotis Filis; Victoria Tessyman; Hazel Kinnell; Andrew J Childs; Nicola K Gray; Richard A Anderson (PLoS ONE)
Germ cell development and primordial follicle formation during fetal life is critical in establishing the pool of oocytes that subsequently determines the reproductive lifespan of women. Fragile X-associated primary ovarian insufficiency (FXPOI) is caused by inheritance of the FMR1 premutation allele and approximately 20% of women with the premutation allele develop ovarian dysfunction and premature ovarian insufficiency. However, the underlying disease mechanism remains obscure, and a potential role of FMRP in human ovarian development has not been explored. We have characterised the expression of FMR1 and FMRP in the human fetal ovary at the time of germ cell entry into meiosis through to primordial follicle formation. FMRP expression is exclusively in germ cells in the human fetal ovary. Increased FMRP expression in germ cells coincides with the loss of pluripotency-associated protein expression, and entry into meiosis is associated with FMRP granulation. In addition, we have uncovered FMRP association with components of P-bodies and stress granules, suggesting it may have a role in mRNA metabolism at the time of onset of meiosis. Therefore, this data support the hypothesis that FMRP plays a role regulating mRNAs during pivotal maturational processes in fetal germ cells, and ovarian dysfunction resulting from FMR1 premutation may have its origins during these stages of oocyte development.